Information and communication technologies and their influence on the learning of the course of mining and the environment in the students of the professional academic school of mine engineering at the National University of Huancavelica - 2017 - FelicRamírez Rosalesisimo German, Felisícimo German (2020)
The academic training of future mining engineer and significance of particular importance, hence our research problem says: What influence does the application of Information and Communication Technology in learning the subject of Mining and Environment students Professional Academic School of Mining Engineering of the Universidad Nacional de Huancavelica – 2009, The research is quantitative, applied type, level of explanation, pre-experimental method and experimental design. The non-probabilistic sample was taken; we conclude that the Information and Communication Technology has significantly improved not only statistically but also pedagogical and educational learning of the subject of Mining and Environment